Electrical contact resistance in graphite–graphene contacts from ab initio methods. (17th July 2018) - Jovell, Ferran; Cartoixà, Xavier
Abstract: We study the ballistic transmission and the contact resistance ( R c ) of a graphite–graphene contact in a top contact geometry from first principles. We find that the calculated R c 's depend on the amount of graphene–graphite overlap, but quickly saturate for transfer lengths of the order of a few tens of Å. For contacts overlapping more than this transfer length, the R c can be lower than the 100 mark. On the other hand, edge graphite–graphene contacts are expected to have very low contact resistance.